Odpowiedzi

2010-02-09T14:31:59+01:00
A)45x²-18x=-12+45x²
-18x=-12/:18
-x=- 2/3
x=2/3

b)x²+35x-50=4x+x²-2x-28
x²+35x-4x-x²+2x=-28+50
33x=22/:33
x=2/3

c)nie wiem gdzie się kończy nawias:(
2010-02-09T14:39:14+01:00
A)9x(5x-2)=-12+45x²
L(2/3) = 9*2/3(5*2/3 -2) = 6( 10/3 - 6/3) = 6 *4/3 = 8
P(2/3) = -12 + 45*(2/3)² = -12 + 45*4/9 = -12 + 20 = 8
L(2/3) = P(2/3)
x = 2/3 jest rozwiazaniem równania

b)x(x+35)-50=x(4+x)-2(x+14)
L(2/3) = 2/3( 2/3 +35) - 50 = (2/3)*(107/3) -50 = 214/9 - 50 = 23 i 7/9 - 50=
= - 26 i 2/9
P(2/3) = 2/3(4 + 2/3) -2( 2/3 + 14) = (2/3) *(14/3) - 2*(44/3) = 28/9 - 88/3=
= 28/9 - 264/9 = - 236/9 = -26 i 2/9
L92/3) = P(2/3)
x = 2/3 jest rozwiazaniem równania

8(3x²-x-10) = 24x²+8
L(2/3) = 8 [3*(2/3)² - 2/3 -10] = 8[ 3*4/9 - 2/3 -10] = 8[ 4/3 -2/3 -10] =
= 8[ 2/3 - 10] = 8*(-9⅓)= 8*(-28/3) = - 224/3 = - 74⅔
P(2/3) = 24*(2/3)² + 8 = 24*(4/9) + 8 = 32/3 + 8 = 10⅔ + 8 = 18⅔

L(2/3)≠L(2/3)
x = 2/3 nie jest rozwiazaniem równania
2010-02-09T14:43:28+01:00
9x(5x-2)=-12+45x²
9*⅔ (5*⅔-2)=-12+45*(⅔)²
6(5⅔-2)=-12+45*4/9
6*17/3-12=-12+20
34-12=8
22=8
L≠P

x(x+35)-50=x(4+x)-2(x+14)
x²+35x-50=4x+x²-2x-28
(⅔)²+35*⅔-50=4*⅔+(⅔)²-2*⅔-28
4/9 +23⅓-50=2⅔+4/9 -1⅓-28
4/9+70/3-50=8/3+4/9-4/3-28
4/9+210/9-50=24/9+4/9-12/9-28
214/9-50=16/9-28
23 7/9-50=1 7/9-28
-26 2/9=-26 2/9
L=P

8(3x²-x-10=24x²+8
24x²-8x-80=24x²+8
-8x=80+8
-8x=88
-8*⅔=88
-16/3=88
-5⅓=88
L≠P